MEDIA JOURNAL-Course: Religion, Homosexuality and Society - Denison, Barbara (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Now that you have collected a variety of media references to homosexuality and culture, please follow these few guidelines for completing your journal.